(untitled) (Communications in Computational Physics, 2018)
A significant step towards the comprehensive solution of the important new fundamental control problems of high-temperature plasma of toroidal configuration is made by utilizing heterogeneous mini-supercomputers of NIISI RAS (Scientific Research Institute of System Development, Russian Academy of Science). The basic components of hardware and software modeling system and automatic real-time plasma feedback control are developed and implemented. The system is named HASP CS (Hardware-Software Plasma Control System). It is based on a fundamentally new, more accurate and reliable control algorithm using a solution with a given accuracy of a number of inverse diagnostic problems by ϵ-nets. The possibility of an application of the proposed technique during discharge time to provide feedback control of the boundary and internal plasma parameters is demonstrated. It is shown that the complex allows investigating the processes in currently operated and designed fusion devices and solving problems of fusion application for energy production. The recommendations to the engineering implementation of plasma control systems are made. The directions for further research are formulated.